Development of Shigella flexneri Detection Method by Real-Time Polymerase Chain Reaction Targeting the sfmD Gene - Nurjayadi, Muktiningsih; Azizah, Puan Aqila; Setiawan, Agus; Sihombing, Ananda Indah Putri; Fitriyanti, Anisa; Grace, Grace; Putri, Gusti Angieta; Angelina, Helzi; Musie, Royna Rahma; Declan, Jefferson Lynford; Putri, Gladys Indira; Juliansyah, Dandy Akbar; Fatimah, Siti; Fahriza, Tiara; Kartika, Irma Ratna; Kurniadewi, Fera; Novitasari, Novitasari; Abomoelak, Bassam; El Enshasy, Hesham Ali; Chen, Shyi-Tien (Makara Journal of Science, 2025)
Shigella flexneri can cause shigellosis, which results in high fever, vomiting, diarrhea, or death. This study developed a detection method based on real-time polymerase chain reaction that targets the sfmD gene of S. flexneri given that the virulence factor encoded by this gene is thought to facilitate adhesion to a host surface. The proposed method involves primer design, DNA isolation, the optimization of primer annealing temperature, and confirmation, specificity, and sensitivity tests. A sfmD primer with an amplicon length of 155 bp was annealed to the target DNA at an optimized temperature of 60 ℃ (range 54 °C–62 °C). This primer pair amplified the target sequences at a cycle threshold (Ct) of 15.11 ± 0.38 and a melting temperature of 82.41 ± 0.01 ℃. The primer specificity test showed that the primer distinguished S. flexneri from nontarget bacteria. The findings also revealed that the primer detected S. flexneri down to a limit of 16 pg/μL at a Ct of 26.68, equivalent to 2.79×102 CFU. Overall, the sfmD primer can effectively amplify S. flexneri DNA. Future research can be directed toward the detection of S. flexneri in artificially contaminated food samples to validate the real-food applicability and strengthen its potential use in food safety monitoring and clinical diagnostics.